Teaching Moral Philosophy through Literature Circles. - Dyk, T.
How do you effectively teach moral philosophy to classes of twenty to thirty-five students who come from diverse national, ethnic, religious, linguistic, and educational backgrounds, and most of whom have little or no interest in philosophy? In seeking ways to create a course that is relevant, practical, and engaging, I hit upon the idea of adapting literature circles to the study of moral philosophies. In this paper, I contextualize the need for an approach that promotes individual student responsibility within a teamwork context, introduce the appropriateness and adaptability of the literature circles concept in a philosophy classroom, and uncover the theoretical structure underneath the strategy in order to make it more adaptable to other classrooms and courses.